Machine learning-based state of charge estimation: A comparison between CatBoost model and C-BLSTM-AE model - Abderrahim Zilali; Mehdi Adda; Khaled Ziane; Maxime Berger (Machine Learning with Applications)
The State of Charge (SOC) is a key metric within a Lithium-ion battery management system (BMS). Accurate SOC estimation is essential for enhancing battery longevity and ensuring user safety, making it a critical component of an effective BMS. Although SOC estimation has become an active research area for the machine learning (ML) community, only a handful of works have considered its estimation at negative temperatures. This paper proposes the application of two machine learning-based approaches for SOC estimation that perform well at wide range of temperatures (positive and negative) and varying dynamic loads. The first one is a hybrid deep learning approach based on the Convolutional BLSTM Auto-Encoder (C-BLSTM-AE) model that relies on extracting abstract features from input data. The second one is a CatBoost model that leverages the gradient boosting technique to enhance the prediction made by its constituent trees. The performance of the models is evaluated by comparing their regression accuracy and computational resource utilization. The C-BLSTM-AE model achieves a low Mean Absolute Error (MAE) of 0.52 % under fixed ambient temperature conditions and maintains a MAE of 1.03 % for variable ambient temperatures. The CatBoost model achieves a MAE of 0.69 % with fixed temperature settings and a MAE of 1.09 % under variable temperature conditions.